A low-cost measurement device for recording perceptions of thermal comfort - Molina J.R. (2020)
In this article, we describe the implementation of a low-cost device that registers perceptions of thermal comfort. The parameters of relative humidity (RH), temperature, thermal sensation (cold, cool, neutral, warn, hot) and clothing worn by people are collected. The design and validation of the device in an indoor environment are explained, and the calibration curves of the temperature and relative humidity sensors are obtained. The measurement results for the device from 10 people are shown. The study was carried out in the village of Imata (high Andean zone), at 4700 masl in the south of Peru. © Published under licence by IOP Publishing Ltd.